Short Review: Biowaste as A Source of Silica and Its Application as A Filler to Fabricate The Superhydrophobic Silica-Based Coating - Nur Fatihah Mohd Fadzil; Muhammad Salihin Zakaria; Razif Muhammed Nordin; Khairul Anwar Abdul Halim; Nur Farhana Hayazi; Lokman Hakim Ibrahim (International Journal of Nanoelectronics and Materials (IJNeaM), 2024)
Silica (SiO2) plays a major key ingredient in producing products such as toothpaste, ceramics, and paints, to name a few, as it acts as a stabilizing agent, filler and additive. Due to its excellent properties, the use of high-purity SiO2 in industrial applications is favourable. Unfortunately, high-purity SiO2 is expensive. Tetraethyl Orthosilicate (TEOS) is an example of a SiO2 precursor that is costly and harmful, yet frequently employed. This paper provides a short review of the advantages of biowaste materials as SiO2 precursors and their role as fillers in the fabrication of superhydrophobic coating. Researchers nowadays are attempting to lower the expense of employing high-purity SiO2 by extracting silica from biowaste using many methods such as acid leaching and alkali treatment as this option is highly sustainable. The growth of agricultural industries is exponential due to the increase in biowaste production. Therefore, this is one of the ways to utilize the use of biowaste in combatting the environmental issues regarding excess biowaste and receding pure resources. SiO2 from biowaste also can be utilized as filler and used to develop superhydrophobic coating, providing numerous potential applications.